PERANCANGAN KNOWLEDGE MANAGEMENT SYSTEM UNTUK PENINGKATAN KOMPETENSI PEMERIKSA DALAM PEMERIKSAAN LAPORAN KEUANGAN (Studi Kasus BPK RI Perwakilan Provinsi Banten) - , Berbudi Bowo Laksono; , Noor Akhmad Setiawan, S.T., M.T., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Knowledge Management System development is one of a main project of application development in BPK's IT Strategic Planning. Knowledge Management implementation will give several benefits to organization such as